Analisis Buku Ajar Bahasa Indonesia Kelas IV Edisi 2021 dan Edisi Revisi 2023 Kurikulum Merdeka Berdasarkan Kelayakan Buku BNSP Menggunakan Genre Based Approach - Sectio Firdaus; Panca Dewi Purwati (LPPM Institut Pendidikan Nusantara Global, 2026)
Indonesia’s education system is undergoing a significant transformation through the implementation of the Kurikulum Merdeka, which necessitates comprehensive adjustments to instructional tools by both the government and educators. A crucial element in this transition is the availability of relevant and high-quality teaching materials. Therefore, continuous evaluation of textbook feasibility is essential to ensure effective teaching and learning processes in schools.This study aims to evaluate and compare the feasibility of Grade IV Indonesian language core textbooks in the Kurikulum Merdeka, specifically between the 2021 initial edition and the 2023 revised edition. The evaluation is based on the standards set by the National Education Standards Agency (BSNP), covering four key aspects: content, presentation, language, and graphics. Additionally, the analysis incorporates the pedagogical framework of the Genre-Based Approach (GBA). This research employs a descriptive qualitative design, using documentation study as the primary data collection method. The research instruments were validated by subject-matter and language experts, achieving average scores of 3.63 and 3.25, both categorized as “Very Good”. The findings indicate that the 2021 edition is generally less feasible due to limitations in differentiation features, less coherent instructional transitions, and dense visual layouts. In contrast, the 2023 revised edition demonstrates notable improvements, including better alignment with Learning Outcomes (Capaian Pembelajaran), more systematic implementation of GBA stages, and a more ergonomic and inclusive design. In conclusion, the 2023 revised edition is a higher-quality and more adaptive instructional resource that better meets the demands of the national curriculum